Strategic consensus predicting outputs of team performance - Puente-Palacios, Katia (2015)
Strategic consensus in work teams is a group process related to the shared comprehension among team members of the strategies defined to attain work goals. This study aimedto verify the predictive power of strategic consensus in relation to team performance. The prediction model was constructed based on data collected from teachers and coordi-nators of 70 educational institutions in Ecuador. The individual data were aggregated per institution to obtain group level scores. The results indicate that strategic consensus predicts about 6% of the team performance as rated by the coordinator. We concluded that more studies are required to gain a better understanding of the role of strategic consensus in workteams.